Consumer Legal Protection from the Decoy Effect Through Digital Literacy - Afrilia Cahyani; Fadia Fitriyanti; Jamaluddin Ahmad; Pratiwi Ramlan (Susbtantive Justice International Journal of Law, 2022)
The millennial and generation Z tend to experience the negative impact of the decoy effect, so a consumer protection law is required. The purpose of this study is to demonstrate the negative impact of the decoy effect and the importance of consumer protection through digital literacy. A quantitative descriptive approach was used with millennial and generation Z research subjects who were given a choice of products using bait items. According to the study's findings, respondents are susceptible to the decoy effect, so consumers have the right to know before making a decision. The findings of this study contribute to the public's understanding and provision of suggestions or criticism, as well as to the government's formulation of consumer protection policies, particularly for the millennial and generation Z generations. The implication is that existing consumer protection laws must be flexible, rational, and based on digital literacy. Legal certainty as a form of consumer legal protection to achieve equality in an engagement as a concept for those who make transaction.